Mobilome-associated resistome in the Pasteurellaceae family and characterization of small RNAs transported by extracellular vesicles produced by Actinobacillus pleuropneumoniae - Silva, Giarlã Cunha da (2022)
The Pasteurellaceae family comprises several species of Gram-negative, commensal or pathogenic bacteria of human and animal hosts. Some members of the Pasteurellaceae family are responsible for causing diseases of economic impact in food-producing animals, such as swine. In this sector, significant expenses are associated with the use of antimicrobials for the treatment of infections caused by species of the Pasteurellaceae family, which are often persistent and multidrug- resistant. Actinobacillus pleuropneumoniae (App) is a member of the Pasteurellaceae family and causes porcine pleuropneumonia, responsible for important economic losses in pig farming worldwide. A. pleuropneumoniae is a primary pathogen and has several virulence factors such as: capsule, LPS, iron siderophores and Apx exotoxins. In addition, they are capable of producing extracellular vesicles (BEVs – Bacterial Extracellular Vesicles), which represents another associated virulence factor, given the involvement in the dissemination of mobile genetic elements (MGEs) and antimicrobial resistance genes (AMR) and innovative abilities that leverage the virulence of App. Thus, the objectives of this work were: i. to evaluate the representativeness of MGEs associated with AMR in members of the Pasteurellaceae family, including App and ii. characterize the BEVs produced by App and their nucleic acid content, focusing on RNA and virulence. The investigation of the resistome associated with the mobilome in Pasteurellaceae was carried out from in silico analysis using complete genomes available in databases in order to identify and characterize MGEs with emphasis on the presence of resistance genes associated with these elements. Through these analyzes, 20 novel integrative and conjugative elements (ICEs) and 23 novel prophages were found, in addition to expanding the characterization of elements previously described for the family. From the results obtained, it was found that MGEs are responsible for carrying most of the resistance genes identified in bacteria of the Pasteurellaceae family, and can be disseminated by different mechanisms of horizontal gene transfer (HGT), such as vesiduction (via BEVs). Thus, in the second part of the work, the BEVs of App were obtained, characterized and the DNA and RNA content investigated under different conditions. Vesicles were investigated for size, protein and lipid content, including LPS type, and nucleic acid content. The characterization of the BEVs revealed a protein profile similar to that found in the outer membrane of App, highlighting the lipid profile, not investigated so far for this specie. The results revealed that the condition of anaerobic growth affects several aspects of BEV production, such as quantity and relative size. The BEVs carry as nucleic acid content, DNA and RNA, the latter being the most abundant and therefore characterized in this work. Transcriptome analysis of the BEVs produced by App revealed that these vesicles carry several types of RNAs, such as tRNAs and small (sRNAs), the latter of which have already been described for App. In this work, 13 new sRNAs for App were described, 12 of which are present in BEVs. Some sRNAs found in BEVs are enriched in vesicles in relation to cells and are present in the intravesicular portion, protected from the action of nucleases. Among the sRNAs found in the BEVs of App, Rna01, previously identified by our group, was selected for further analysis. Target analysis of this sRNA revealed that it is associated with the regulation of several genes encoding membrane proteins, mainly in response to stress conditions, which was confirmed through quantitative expression analyses. Through analyzes carried out with mutant strains for Rna01, it was observed that the production of BEVs was also affected, revealing the participation of this sRNA in this process in App. This work provides a complete characterization of MGEs and AMR in the Pasteurellaceae family and is also the first work to perform a complete characterization of BEVs produced by App under different conditions, in addition to confirming the presence and functionality of sRNAs in BEVs produced by App. Thus, several unpublished information and guidelines for actions aimed at controlling porcine pleuropneumonia. Keywords: Pasteurellaceae. Actinobacillus pleuropneumoniae. Pleuropneumonia. Mobile genetic elements. Antimicrobial resistance. Bacterial extracellular vesicles. Nucleic acids. small RNAs.